Implementasi Model Service-Oriented Architecture (SOA) dalam Perancangan Sistem Informasi UMKM - Nur Hadian; Mujibul Hakim; M. Rudi Fanani (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
This research focuses on developing a Small and Medium Enterprises (SMEs) Information System architecture using the Service-Oriented Architecture (SOA) and microservices approach. This study successfully integrated SME system services and functionalities encompassing accounting management, financial management, product analysis, stock management, invoicing, and taxation services within an SOA structure. Adopting the principles of microservices, each service was able to isolate information and ensure consistency within its scope. Using CI/CD, service mesh, and the Kubernetes platform facilitated efficient and secure code delivery and effective inter-service communication management. This research demonstrates the importance of service-oriented architecture and microservices in building a modular, flexible, and customizable SME information system that can reuse resources and reduce dependency on back-end applications. As a result, the system produced can be easily adapted and enhanced to meet changing policy and business needs.